Opvoedkundige Tegnologie / Educational Technology: Die rol van die instrukteur in die moderne onderrig-leersituasie - Bouwer, U. (Scientia Militaria - South African Journal of Military Studies, 2012)
In the modern teaching-learning situation the role of the instructor has changed from expert, authoritarian and only source of information to that of manager of training. This includes planning, organizing, leading and control. This article gives an indication of what this implies